Sparstolonin B exerts beneficial effects on prostate cancer by acting on the reactive oxygen species‐mediated PI3K/AKT pathway - Liu, Shaozhuang (J Cell Mol Med, 2021)
Prostate cancer is a major health concern in males worldwide, owing to its high incidence. Sparstolonin B (SsnB), a component of the Chinese herbal medicine Sparganium stoloniferum, is used to treat many diseases. However, the effects and mechanisms of action of SsnB in prostate cancer have not yet been reported. In this study, we evaluated the effects of SsnB on cellular processes and tumour growth. In particular, we verified that SsnB could inhibit the proliferation, migration and invasion of prostate cancer cells and induce apoptosis by activating G2/M phase arrest in vitro based on a series of cytological experiments. In vivo, we found that SsnB could inhibit tumour growth in nude mouse xenograft models. We further confirmed that SsnB could repress the PI3K/AKT pathway by increasing reactive oxygen species (ROS) accumulation and oxidative stress. Collectively, SsnB inhibits tumour growth and induces apoptosis in prostate cancer via the suppression of the ROS‐mediated PI3K/AKT pathway and may be a new alternative to adjuvant therapy for prostate cancer.